Handbook of research on green technologies for sustainable management of agricultural resources - Sengar, Rakesh S.; Chaudhary, Reshu; Bhadauria, H., 1961- (Advances in environmental engineering and green technologies (AEEGT) book series., 2022)
"As agricultural productivity has been gaining prominence in recent years and is now become the important points for the modern agriculture, this book covers different eco-friendly technologies for the sustainable management of natural resources"--